43.8k views
5 votes
Simplify the expression (4x − 3)(x + 5). 4x2 − 17x + 15 4x2 − 17x − 15 4x2 + 17x + 15 4x2 + 17x − 15

2 Answers

0 votes
a)
(4x-3)(x+5)=


*(a+b)(c+d)=ac+ad+bc+bd


Soo..


4x*x+4x*5-3*x-3*5=


=4 x^(2) +20x-3x-15


=4x^(2) +17x-15

b)
4x^(2) -17x+15=


=(4x-5)(x-3)

c)
4 x^(2) -17x-15=


=(4x+3)(x-5)

d)
4 x^(2) +17x+15=

=(4x+5)(x+3)


e)
4 x^(2) +17x-15=

=(4x-3)(x+5)




User Sujesh Arukil
by
6.6k points
1 vote
There are mnemonic acronyms out there for reminding you how to do this. I think of it simply as using the distributive property.
(4x-3)(x+5) = 4x(x+5) -3(x+5)
then again
= (4x² +20x) + (-3x -15)
= 4x² + (20-3)x -15 . . . . . . . combine like terms
= 4x² +17x -15
User Friesgaard
by
7.0k points